Approximation by Some Stancu Type Linear Positive Operators - Sharma, Prerna (Journal of Nepal Mathematical Society, 2022)
Present paper is the study about Stancu type generalization of modified Beta-Szasz operators and their q-analogues. We obtain some approximation properties for these operators and estimate the rate of convergence by using the first and second order modulus of continuity. Author also investigates the statistical approximation properties of the q-Beta-Stancu operators using Korokvin theorem.